2013
DOI: 10.1007/s11665-013-0584-1
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Mechanical Characterization of SMAs Fiber-Reinforced Hybrid Composite Under Uniaxial Loading

Abstract: This paper presents an experimental and theoretical investigation on the macroscopic mechanical behavior of shape memory alloys (SMAs) fiber-reinforced glass/resin composite subject to uniaxial loading at ambient temperature. A series of unidirectional SMAs reinforced composite laminates is fabricated through vacuum-assisted resin injection. Scanning electron microscopy is conducted to evaluate the interfacial cohesive quality between SMAs fiber and matrix. A theoretical model is proposed based on the SMAs pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Tensile failure damage mechanics of the SMA/GFRP composite indicating the SMA fiber fracture and debonding. Photograph courtesy of Lei et al . Copyright 2013.…”
Section: Shape Memory Hybrid Compositesmentioning
confidence: 98%
See 3 more Smart Citations
“…Tensile failure damage mechanics of the SMA/GFRP composite indicating the SMA fiber fracture and debonding. Photograph courtesy of Lei et al . Copyright 2013.…”
Section: Shape Memory Hybrid Compositesmentioning
confidence: 98%
“…Lei et al investigated SMHCs with sandwiched SMA wires in a glass fiber/resin matrix and showed improvement in mechanical strength and stiffness of the SMHC with increasing number of wires, as depicted in Figure a,b . In a recent study, Taheri-Behrooz et al showed that, for elevated temperature applications, SMA wire reinforcement can be integrated in composites having lower strength/stiffness compared to that in the austenite phase of SMA.…”
Section: Shape Memory Hybrid Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…[20] The tightening torque τ was used instead of the normal force P w in the numerical simulation, the relation can be written as,…”
Section: Failure and Degradation Criteriamentioning
confidence: 99%